Plasma and Gas‐based Semiconductor Technologies for 2D Materials with Computational Simulation & Electronic Applications - Kim, Changmin; Kim, Muyoung; Kim, Seongho; Kang, Minji; Choi, Min Sup; Kim, Hyeong‐U (Advanced electronic materials, 2024)
The technique of plasma processing is beneficial for wafer cleaning and precision etching of integrated circuits and essential in manufacture of advanced semiconductor devices with unmatched perfection. Research on two‐dimensional (2D) materials, such as transition metal dichalcogenides(TMDs), offers a promising solution to the challenges in semiconductor miniaturization. TMDs, with their atomic layer thicknesses and silicon‐like bandgaps, can be integrated using existing plasma systems. Different 2D crystal structures, such as 1T and 2H configurations, exhibit distinctive properties. Computational approaches are also developed to provide guidelines for controlled synthesis and etching of large‐scale and high‐quality 2D materials. Plasma/gas‐surface interactions during the synthesis, etching, and phase transformation of 2D materials are explored using atomistic simulations such as density functional theory and molecular dynamics. The reaction energetics, chemical species, and associated kinetics are discovered in the simulation study. These results decipher various mechanisms of 2D materials processing at the microscopic scale and predict certain optimal process parameters. Plasma/gas‐based semiconductor technologies are crucial in electronics because they enable production of advanced semiconductors. Plasma/gas etching allows precise and selective removal of material and plasma‐enhanced chemical vapor deposition enhances chemical reactions for efficient film deposition; therefore, these processes are majorly important for harnessing 2D materials in electronic applications. Plasma processing is the key  advanced semiconductor production, enabling precise etching and integrating thin, silicon‐like 2D materials like transition metal dichalcogenides. Computational simulations guide synthesis and etching, optimizing processes for electronic applications. This technology is essential for miniaturizing semiconductors and efficient film deposition.